2018
DOI: 10.3390/ijms19020587
|View full text |Cite
|
Sign up to set email alerts
|

Integrins Were Involved in Soybean Agglutinin Induced Cell Apoptosis in IPEC-J2

Abstract: Soybean agglutinin (SBA), is a non-fiber carbohydrate related protein and a major anti-nutritional factor. Integrins, transmembrane glycoproteins, are involved in many biological processes. Although recent work suggested that integrins are involved in SBA-induced cell-cycle alterations, no comprehensive study has reported whether integrins are involved in SBA-induced cell apoptosis (SCA) in IPEC-J2. The relationship between SBA and integrins are still unclear. We aimed to elucidate the effects of SBA on IPEC-J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Recently, it was reported that; soybean or soybean products can lead to some deleterious effects on the gastrointestinal tract. Such effects are related to abnormal cell cycle (Pan et al 2017), cell apoptosis (Pan et al 2018b), or altering the normal microbial composition of the gut (Pan et al 2018a). Several studies have been conducted on sheep to evaluate the effects of Nigella sativa (NS) on different blood biochemical parameters in different physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that; soybean or soybean products can lead to some deleterious effects on the gastrointestinal tract. Such effects are related to abnormal cell cycle (Pan et al 2017), cell apoptosis (Pan et al 2018b), or altering the normal microbial composition of the gut (Pan et al 2018a). Several studies have been conducted on sheep to evaluate the effects of Nigella sativa (NS) on different blood biochemical parameters in different physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The release of alkaline phosphatase in the intestinal epithelial cells increases intestinal membrane permeability, elevating the occurrence of inflammation and infections (Bates, Akerlund, Mittge, & Guillemin, ; Geddes & Philpott, ), and decrease in TEER value. The increase in intestinal membrane permeability results in the reduction in tight junction integrity, disruption of cell‐to‐cell adhesions and decrease in cell viability and causes intestinal villus atrophy (Grant, Ewen et al, ; Pan et al, ; Pan, Zhao et al, ; Zhao et al, ), affecting cellular morphology, metabolism and proliferation (Pan et al, ). Several studies reported that the supplementation of SBA in intestinal epithelial cells decreased the TEER value, hence affecting membrane permeability (Dalla Pellegrina et al, ,; Pan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ingestion of SBA can decrease the intestinal health by affecting intestinal structures (Fasina et al, ), barrier functions (Pan, Farouk et al, ; Pan et al, ), mucosal immune systems (Greer & Pusztai, ) and balance of the intestinal flora (Pusztai Greer & Grant, ). The anti‐nutritional effects of SBA are reportedly varying in animals based on species, age and concentration of lectins (Pan, Zhao et al, ); these effects are greater in animals with single stomach compartment than animals with complex stomach compartments (Grant, Holland, Thomas, King, & Liesman, ). The SBA decreases membrane barrier functions in the epithelial cells by increasing membrane permeability, inhibits cell viability and decreases tight junction protein (Occludin and claudin) expression (Pan, Farouk et al, ; Pan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The researches in cellular level indicated that SBA can damage the interaction between cell-to-cell, increase cell apoptosis rates, inhibit cell proliferation, and affect some signal transduction pathways [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%